Corruption and government : causes, consequences, and reform - Rose-Ackerman, Susan; Palifka, Bonnie J. (Cambridge : Cambridge University Press, 2016)
The second edition of Corruption and Government updates Susan Rose-Ackerman's 1999 book to address emerging issues and to rethink old questions in light of new data. The book analyzes the research explosion that accompanied the fall of the Berlin Wall, the founding of Transparency International, and the World Bank's decision to give anti-corruption policy a key place on its agenda. Time has vindicated Rose-Ackerman's emphasis on institutional reform as the necessary condition for serious progress. The book deals with routine payoffs and with corruption in contracting and privatization. It gives special attention to political corruption and to instruments of accountability. The authors have expanded the treatment of culture as a source of entrenched corruption and added chapters on criminal law, organized crime, and post-conflict societies. The book outlines domestic conditions for reform and discusses international initiatives - including both explicit anti-corruption policies and efforts to constrain money laundering.
Machine generated contents note: Introduction; 1. What is corruption and why does it matter?; Part I. Corruption as an Economic Problem: 2. Bureaucratic corruption; 3. Corruption in procurement and privatization; 4. Reducing incentives and increasing costs; 5. Civil service reform and bureaucratic reorganization; 6. Using the criminal law to deter bribery and extortion; Part II. Corruption as a Cultural Problem: 7. Culture and corruption; Part III. Corruption as a Political Problem: 8. Politics, corruption, and clientelism; 9. Organized crime, corruption, and money laundering; 10. Corruption in post-conflict state building; 11. Democracy: corruption, connections, and money in politics; 12. Accountability beyond the ballot box; Part IV. Reform Agendas -- Domestic Political Will and International Influence: 13. Domestic conditions for reform; 14. The role of the international community; 15. The role of international cooperation: states, firms, banks, and organized crime; Part V. Conclusions: 16. Conclusions.
Title from publisher's bibliographic system (viewed on 08 Mar 2016).
Keywords: Political corruption; Political corruption -- Economic aspects